2017
DOI: 10.33549/physiolres.933583
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Association of Lipoprotein (a) With Markers of Insulin Resistance in Dyslipidemic Subjects

Abstract: Lipoprotein (a) [Lp(a)] is an LDL-like particle that contains an apolipoprotein B100 molecule covalently bound to a plasminogen-like glycoprotein, apolipoprotein (a) [apo(a)]. Epidemiological evidence supports a direct and causal association between Lp(a) levels and coronary risk. On the contrary, a few prospective findings demonstrate inverse association of Lp(a) levels with risk of type 2 diabetes (T2DM). The aim of our study was to evaluate the association of Lp(a) with indicators of insulin resistance (IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Borai et al (2011) have shown that HbA1c may serve as a simple and reliable marker for IR in adults with normal glucose tolerance. Vaverková et al (2017) observed an inverse association between lipoprotein-a and IR as well as metabolic syndrome that precedes an overt T2DM diagnosis.…”
Section: Introductionmentioning
confidence: 89%
“…Borai et al (2011) have shown that HbA1c may serve as a simple and reliable marker for IR in adults with normal glucose tolerance. Vaverková et al (2017) observed an inverse association between lipoprotein-a and IR as well as metabolic syndrome that precedes an overt T2DM diagnosis.…”
Section: Introductionmentioning
confidence: 89%
“…Although no consensus goal of Lp(a) is established, the general recommendation is to treat other cardiovascular risk factors in patients with high Lp(a) in combination with other hypolipidemic and glucose-lowering drugs [ 2 , 15 ]. At the same time, recent studies have demonstrated that, while increased Lp(a) levels are associated with enhanced atherogenesis, proinflammatory and prothrombotic states [ 16 ], a greater risk of cardiovascular events, and poorer prognosis [ 2 , 15 , 17 , 18 ], the decreased serum concentrations of Lp(a) are related to the insulin resistance state [ 19 ]. These findings suggest that any shift (either to increase or decrease) of Lp(a) might be associated with an unfavorable outcome and should be monitored, so the association between Lp(a) levels and cardiometabolic disease might be U-shaped.…”
Section: Discussionmentioning
confidence: 99%
“…T2D can have a lag phase of 10-20 years before it is diagnosed, and in the preceding timespan, patients will develop insulin resistance and elevated insulin levels. Several studies have shown an inverse association between insulin levels and Lp(a) levels (11), even before a frank diagnosis of T2D is made (12,13). Furthermore, physiological doses of insulin have been suggested to suppress apolipoprotein(a) mRNA and protein production in cynomolgous monkey hepatocytes (14).…”
Section: Sotirios Tsimikas 2 Editorial Boardmentioning
confidence: 99%